Blood use in patients receiving intensive chemotherapy for acute leukemia or hematopoietic stem cell transplantation: the impact of a health system–wide patient blood management program. Issue 9 (3rd July 2017) - Leahy, Michael F.; Trentino, Kevin M.; May, Colleen; Swain, Stuart G.; Chuah, Hun; Farmer, Shannon L.
Abstract : BACKGROUND: Little is published on patient blood management (PBM) programs in hematology. In 2008 Western Australia announced a health system–wide PBM program with PBM staff appointments commencing in November 2009. Our aim was to assess the impact this program had on blood utilization and patient outcomes in intensive chemotherapy for acute leukemia or hematopoietic stem cell transplantation. STUDY DESIGN AND METHODS: A retrospective study of 695 admissions at two tertiary hospitals receiving intensive chemotherapy for acute leukemia or undergoing hematopoietic stem cell transplantation between July 2010 and December 2014 was conducted. Main outcomes included pre–red blood cell (RBC) transfusion hemoglobin (Hb) levels, single‐unit RBC transfusions, number of RBC and platelet (PLT) units transfused per admission, subsequent day case transfusions, length of stay, serious bleeding, and in‐hospital mortality. RESULTS: Over the study period, the mean RBC units transfused per admission decreased 39% from 6.1 to 3.7 (p < 0.001), and the mean PLT units transfused decreased 35% from 6.3 to 4.1 (p < 0.001), with mean RBC and PLT units transfused for follow‐up day cases decreasing from 0.6 to 0.4 units (p < 0.001). Mean pre‐RBC transfusion Hb level decreased from 8.0 to 6.8 g/dL (p < 0.001), and single‐unit RBC transfusions increased 39% to 67% (p < 0.001). This reduction represents blood product cost savings of AU$694, 886 (US$654, 007). There were no significant changes in unadjusted or adjusted length of stay, serious bleeding events, or in‐hospital mortality over the study. CONCLUSION: The health system–wide PBM program had a significant impact, reducing blood product use and costs without increased morbidity or mortality in patients receiving intensive chemotherapy for acute leukemia or hematopoietic stem cell transplantation.